1982
DOI: 10.1161/01.atv.2.6.475
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional changes of rhesus serum low density lipoproteins during cycles of diet-induced hypercholesterolemia.

Abstract: Over the course of a 2-year study, two male rhesus monkeys underwent episodes of diet-induced hypercholesterolemia (from a diet supplemented with 25% coconut oil and 2% cholesterol) followed by regression phases in which the animals received a low fat Purina chow diet. During the induction of hypercholesterolemia, serum cholesterol, apo B, saturation of low density lipoprotein (LDL) cholesteryl ester fatty acyl chains, and the ability of the serum to stimulate cholesterol esterification by smooth muscle cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 25 publications
0
7
1
1
Order By: Relevance
“…5 Blood was collected frorti the femoral vein of monkeys anesthetized with ketamine and the serum was separated by centrifuging the blood at 4°C for 30 minutes at 1000 g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Blood was collected frorti the femoral vein of monkeys anesthetized with ketamine and the serum was separated by centrifuging the blood at 4°C for 30 minutes at 1000 g.…”
Section: Methodsmentioning
confidence: 99%
“…5 HDL cholesterol was quantitated after the precipitation of the apo B containing lipoproteins from 1 ml serum with 40 IJL\ heparin (5 x 10 6 units/I) and 50 ^l 2 M MnCI 2 . 15 The cholesterol concentration of the supernatant was determined with the Liebermann-Burchard reaction using the Auto Analyzer II.…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lp(a) was first recognized in rhesus monkeys by Fless et al 13 Later, Nevan et al 14 reported a relation between plasma Lp(a) levels, apolipoprotein (a) (apo[a]) isoforms, and low density lipoprotein receptor function. Azrolan et al 15 reported that Lp(a) from cynomolgus monkeys is immunochemically and quantitatively similar to human Lp(a).…”
Section: Studies On Plasma Lp(a) In Macaquesmentioning
confidence: 99%
“…The wisdom of this advice is questionable because several studies (22)(23)(24) show coconut oil, which is rich in caproic (8 : 0) and caprylic (10 : 0) acid as well as lauric (12 : 0) and myristic (12 : 0) acids, raises LDL-C and the TC: HDL-C ratio compared with olive oil or palm olein where the SFA are provided mainly by palmitic acid. Furthermore, coconut oil is relatively atherogenic in animal models especially when fed with dietary cholesterol (25) . In contrast, palm oil, which is rich in palmitic acid, does not have different effects on LDL-C from high oleic acid safflower oil in primates in the absence of dietary cholesterol (26) .…”
Section: Effects Of Different Sfa On Serum Lipids and Lipoproteinsmentioning
confidence: 99%